The Effect of Different Factors on the Strength of Glue Wood Constructions - Makhmatkulov, T.; Boltaev, T.; Isrofilov, Z. (European Journal of Life Safety and Stability (2660-9630), 2022)
One of the promising directions for the manufacture of wooden structures is glued wooden structures. Therefore, studying the influence of various factors on the strength of structures is an important task. Also important is the influence on the strength of such factors as humidity, the presence of knots, oblique layers, etc. The article presents the results of the analysis carried out in this direction.